Anemia Prevention Behavior in Pregnant Women: A Qualitative Study Based on the Health Belief Model at Lere Community Health Center - Yulfiana Yulfiana; Munir Salham; Zhanaz Tasya (PT. Anagata Sembagi Education, 2026)
Anemia in pregnancy remains a significant public health problem that increases the risk of complications for mothers and neonates. The high incidence of anemia in Lere Community Health Center (Puskesmas Lere) working area, 109 cases in 2024, the highest in Palu City, indicates that existing prevention efforts have not been optimal. This qualitative case study aimed to identify and explore behavioral factors in anemia prevention among pregnant women based on the Health Belief Model (HBM). Fifteen informants were selected through purposive sampling, comprising 12 pregnant women in trimesters I–III, one midwife, one posyandu cadre, and one husband. Data were collected through in-depth interviews, observation, and document review, then analyzed using thematic analysis. Results showed that perceived susceptibility and severity toward anemia were generally low because most informants did not fully understand the risks and consequences. Perceived benefits toward Iron Supplementation Tablet (IST/TTD) consumption, nutritious diet, and routine Antenatal Care (ANC) visits were fairly good. Key barriers included IST side effects (nausea, vomiting), habitual tea or coffee consumption, and cultural food taboos. The most influential cues to action stemmed from self-awareness, husband support, midwives, posyandu cadres, and reminder media. Self-efficacy was relatively good but influenced by forgetfulness, physical condition, and family support. It is concluded that anemia prevention behavior is shaped by individual perception, social support, and sociocultural factors. Health education, family involvement, and culturally sensitive approaches are essential to strengthen anemia prevention behavior in pregnant women